Current confinement in EP-VECSELs for high power single-mode operation suitable for passive mode-locking - Dahhan, Imad; Barbarin, Yohan; Hoffmann, Martin; Pallmann, Wolfgang P.; Zaugg, Christian; Golling, Matthias; Suedmeyer, Thomas; Keller, Ursula; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
One of the main advantages of using VECSEL lasers for mode-locked operation is their power scalability. Best performance data available for mode-locked semiconductor lasers have been achieved with optically pumped VECSELs, reaching pulses in the femtosecond regime and average powers in the watt regime.1 This advantage is challenging for electrically pumped VECSELs, where a homogeneous carrier injection into the center must be provided in order to maintain a single-mode operation for large diameter devices. In this paper we investigate the current injection from the bottom contact of a VECSEL design, and estimate the leakage of the hole current. Then we introduce two designs that can reduce the leakage current and enhance the injection into the center of the device, thereby increasing the simulated output power by more than 20% in CW-mode while maintaining an optimal gain profile suitable for single-mode operation. © 2012 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electrically-pumped; Mode-locking; Semiconductor laser; Simulation; VECSEL